Analysis of BSI Smart Agent Fees at Tebuireng Mitra Sejahtera Sharia Micro Finance Institution Based on Islamic Wages - Muhammad Kuruntama Mashari; Masyhudan Dardiri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Financial institutions in Indonesia now have a new breakthrough in providing convenience for customers in transactions, one of which is payment. Payment methods that are usually known to the public in the form of cash, debit cards, credit cards are now financial institutions offering digital service transactions through applications, one of which is the Lantabur Mobile application. Therefore this study aims to find out how effective digital service transactions are through the Lantabur Mobile application in an Islamic economic perspective. Researchers used qualitative research methods with a case study approach. The results of the study show that digital service transactions through the Lantabur Mobile application cannot be said to be effective because they have not met the indicators of effectiveness and are not in accordance with the objectives and implications of maqashid sharia. So it can be concluded that technological developments in the financial sector have brought progress and convenience in transactions. However, research shows that digital service transactions through the Lantabur Mobile application cannot be said to be effective in an Islamic economic perspective because they do not meet the effectiveness indicators and implications of maqashid sharia.